Conflict or dialogue of cultures in the context of current migrations = Conflit ou dialogue des cultures dans le contexte des migrations contemporaines = Il conflitto o il dialogo delle culture nel contesto delle migrazioni attuali - Dupkala, Rudolf (Philosophy and canon law, 2016)
The article analyzes the present-day issue of migration and immigration from theperspective of reformulated concept of axiological pluralism and cultural pluralism. This concept is presented as an alternative to the “anachronistic” project of multiculturalism. The current wave of migration—according to the author—has a twofold effect: it contributes to the rapprochement and mutual enrichment of humanity and human cultures or the escalation of tensions and the outbreak of conflicts arising on the grounds of culture, religion and values. The leitmotif of this work is a reflection on the possibilities, conditions and limitations of the dialogue of cultures. In this context, the author distinguishes between cultures that are proportionate and disproportionate in value. Tolerant coexistence is “possible” only in the culture of commensurate value.